A Study of Vocational Students Perception during Apprenticeship in Insurance Industry - Karin Amelia Safitri (Fakultas Tarbiyah dan Ilmu Keguruan IAIN Kerinci, 2019)
Vocational Higher Education is a formal college providing knowledge as well as preparing the students for six months apprenticeship after five semesters of school. This study is based upon work that the researcher has done to investigate the contribution of this institution especially insurance administration and actuary seen from the student's perspectives for apprenticeship to develop their skills. This study used qualitative data which were collected by interviewing the randomly chosen apprentices and are measured with the questionnaire. The study shows that 58,5% of total apprentices had difficulty when they are doing their job which is caused by what they had to do is a little bit different from the theory taught in college. But they think the lecturers had an important role in learning and gave them many theories before they went to the apprenticeship. The finding revealed that they preferred to learn by watching others working. They watched, learned, and did the job.